STATE REGULATION OF COMPREHENSIVE REGIONAL DEVELOPMENT IN UZBEKISTAN (International journal of artificial intelligence, 2025)
This article is devoted to the issues of state regulation of comprehensive regional development in Uzbekistan. The study analyzes the strategic approaches of economists regarding attracting investments, creating a favorable investment environment, and implementing investment projects in high-tech sectors. Particular attention is paid to the development of a long-term investment strategy and its impact on regional development and economic stability.